Biology, morphology and DNA barcodes of Tessaratoma javanica (Thunberg) (Hemiptera: Tessaratomidae) - Parveen, Shama; Choudhary, Jaipal Singh; Thomas, Asha; Ramamurthy, Vilayanoor Venkataraman (Zootaxa, 2015)
Tessaratoma javanica (Thunberg) (Hemiptera: Tessaratomidae) an important sucking pest of litchi is studied for supplementing information on its biology, morphometrics of life stages and mtCOI (DNA barcodes). More details generated on the study add to the description of stages namely egg, 1st to 5th nymphal instars and adults. The evaluation of morphometrics of the life stages reveal that the progression of growth is more during 2nd to 3rd nymphal stages, and these are critical as far as the growth and development is concerned. The life cycle takes about 141.7±4.25 days; eggs last for 12.81±1.4 days with 97.14±2.86% hatchability; and duration of 1st , 2nd, 3rd, 4th and 5th nymphal instars were 11.69±0.58, 7.23±0.2, 8.63±0.55, 13.04±0.55 and 26.31±0.97 days, respectively. In addition mtCOI analyses have been done employing standard 658 bp barcode fragments facilitating molecular diagnostics of the adults and other life stages and the phylogenetic tree with available sequence in the GenBank.